KESULITAN BELAJAR SISWA PADA KOMPETENSI MEMBUAT KEBAYA MODERN DAN KEMBEN DI SMK NEGERI 8 PADANG - Riani, Aqsya; Yasnidawati, Yasnidawati; Nelmira, Weni (Journal of Home Economics and Tourism, 2014)
The problems in this research is the students seem less able to analyze fashion design, pattern making, students are less precise in cutting, and not good enough in sewing, disadvantaged students in completing the outfit with hand sewing. It is necessary for research on student learning difficulties in making women's fashion competence Making of Modern Kebaya and Kemben. The purpose of this study was to describe the learning difficulties by students in the making of modern kebaya and kemben that includes design analysis, making patterns, cutting material, sewing techniques, and completed the outfit with hand sewing. The type of this research is quantitative descriptive. The population is all students of class XII Department of Fashion Design at SMK N 8 Padang which are 24 persons. Instrument used in this study is questionnaire in the form of Likert scale. Result showed that students learning difficulties there are 33% students have the middle category difficulties in analyzing the design, 46% students have the middle category difficulties in making pattern, 33% students have the middle in sewing, 33% students have the the middle difficulties in complete the outfit with hand sewing. Overall, students' learning difficulties in the competence Making of Modern Kebaya and Kemben as much as 42% with the middle category. Hoped the student can increase their learning system in making kebaya modern dan kemben so they can the get the good achiement. Â  Kata Kunci: kesulitan belajar siswa, kebaya modern dan kemben